2003
DOI: 10.1021/jm0341204
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ergot Alkaloid as a 5-HT1A Inhibitor Produced by Dicyma sp.

Abstract: In the course of a search for small-molecule inhibitors of 5-hydroxytryptamine receptors we have identified a novel ergoline derivative (1) from the fungal culture of Dicyma sp. This compound has a pK(i) of 10.2 versus the 5-hydroxytryptamine(1A) receptor subtype. The structure was elucidated by extensive NMR spectroscopy and mass spectrometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…In comparison, 1 H NMR analysis of a commercial sample of LSD tartrate showed the presence of a molar ratio of 1:1 for tartaric acid:LSD based on the integrals associated with the tartrate methine protons at 4.23 ppm (Supporting Information). The NMR data obtained for 1P‐LSD is consistent with its structure and closely related substances reported before . In the proton NMR spectrum, the chemical shifts linked to the propionyl group overlapped with the resonances associated with one of the methyl groups of the N , N ‐diethylamide group, H‐7α and H‐5β (Figure A), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, 1 H NMR analysis of a commercial sample of LSD tartrate showed the presence of a molar ratio of 1:1 for tartaric acid:LSD based on the integrals associated with the tartrate methine protons at 4.23 ppm (Supporting Information). The NMR data obtained for 1P‐LSD is consistent with its structure and closely related substances reported before . In the proton NMR spectrum, the chemical shifts linked to the propionyl group overlapped with the resonances associated with one of the methyl groups of the N , N ‐diethylamide group, H‐7α and H‐5β (Figure A), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In that regard, a recent claim that EAS genes were horizontally transferred to Clavicipitaceae (Marcet-Houben and Gabaldón 2016) is dubious because it includes gene orthologs and paralogues in the phylogenetic analysis (a typical problem in HGT studies), and because the purported discontinuous distribution among fungal groups is overstated. Though best characterized in Clavicipitaceae and Trichocomaceae, an ergopeptine has been isolated from a Dicyma species (Xylariaceae) (Vazquez et al 2003), and ergot-alkaloid biosynthesis genes or close homologs have been identified in diverse fungi (Gerhards et al 2015) including a Malbranchea sp. (Myxotrichaceae) (Ding et al 2008).…”
Section: Ergot-alkaloid Diversification In the Clavicipitaceaementioning
confidence: 99%
“…Recentemente, esse fungo foi relatado no Japão, colonizando basidiomata de Aphyllophorales (Watanabe et al, 2003). O gênero Dicyma tem despertado interesse, também, no isolamento de novos compostos terapêuticos para uso humano (Vázquez et al,2003). Portanto, a conservação desse fungo é imprescindível para o desenvolvimento de processos e obtenção de produtos de interesse econômico.…”
Section: Dicyma Pulvinata Isolates Colonizing Microcyclus Ulei Stromaunclassified